Screening of new psychoactive substances (NPS) by gas-chromatography/time of flight mass spectrometry (GC/MS-TOF) and application to 63 cases of judicial seizure - Dei Cas, Michele (Forensic Sci Int, 2019)
A screening method for the separation and identification of more than fifty NPS is proposed. The method is based on fast gas-chromatography/time of flight mass spectrometry (FAST-GC/MS-TOF). Thanks to the shorter and narrower capillary column and to the rapid acquisition of the TOF detector a huge number of compounds are separated in a very short time of analysis (10 min). Only a few peaks were overlapped. The possibility to apply deconvolution by the software of the GC/MS-TOF instrument allowed the unequivocal identification also for the superimposed peaks. Linearity and LOD was studied and the method was applied to 63 cases of powders seized by the judicial authority at the airport of Milano Malpensa in Northern Italy in the period 2014–2017.